Issues in local government administration in Nigeria - Zoaka, Yusufu Ali.; Dauda, Saleh (Kongo-Zaria [Nigeria] : Tamaza Publishing, 1998)
This provides an in-depth view of local government administration in Nigeria. It covers of topics like: the concept of local government administration; pre-colonial period; Native Authority reforms; functions of local government councils; problems of local government among others.
Includes bibliographical references (p. 75-79) and index.
lje 28/09/16
Loans
Keywords: Local government; Administration - government; Nigeria